Pengaruh Bahasa Gaul di Media Sosial terhadap Perkembangan Nilai-nilai Karakter Mahasiswi STITMA Yogyakarta Tahun 2024/2025 - Putri Nurkhasanah; Widyaningtyas Kusuma Wardani; Widiyanto Widiyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by concerns about the decline in communication quality and character values among youth due to the use of slang language that does not adhere to proper linguistic norms, particularly through the widespread use of social media. The aim of this study is to examine the influence of slang language used on social media on the development of character values among female students at STITMA Yogyakarta, as well as to explore their perspectives on this phenomenon in daily life. This study employs a quantitative approach with a correlational method. Data collection techniques include questionnaires, interviews, and documentation. The population consists of fourth- and sixth-semester female students from the Islamic Education (PAI) and Arabic Education (PBA) programs, with a sample of 75 students selected using proportionate stratified random sampling. The data were analyzed using validity, reliability, normality, homogeneity tests, and hypothesis testing through the Pearson Product Moment correlation test. The results show that the calculated r-value of 0.967 is greater than the critical r-value of 0.2272, indicating a significant and positive influence between the use of slang language and character values. Thus, slang language is proven to impact the character development of female students in today’s digital era.